Polski leksem "interes" oświetlony ze wszystkich stron = A Polish word "business" (Polish interes) illuminated from all sides - Siatkowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper is divided into four parts. In the first part the role of the concept of "business" (Polish interes) is considered (and comparatively the concept of "need") throughout Polish language development. The second part deals with the prehistory of the word, and therefore the source of this loan and the form and meaning of words derived from it.
Keywords: "interes"; znaczenie; obyczaje; zapożyczenie; słownik; business (interes); meaning; custom; loanword; dictionary